2005
DOI: 10.1111/j.1460-9568.2005.04272.x
|View full text |Cite
|
Sign up to set email alerts
|

NMDA‐receptor blockade by CPP impairs post‐training consolidation of a rapidly acquired spatial representation in rat hippocampus

Abstract: Recent evidence suggests that N-methyl-D-aspartate (NMDA)-receptor mediated plasticity in hippocampus has a more subtle role in memory-based behaviours than originally thought. One idea is that NMDA-based plasticity is essential for the consolidation of post-training memory but not for the initial encoding or for short-term memory. To further test this idea we used a three-phase variant of the hidden goal water maze task. In the first phase, rats were pre-trained to an initial location. Next, intense, massed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
60
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 28 publications
12
60
1
Order By: Relevance
“…This suggests that the "strength" of the encoded representation is weakened under the influence of ketamine (Kentros et al, 1998). Studies have shown that posttraining administration of NMDA antagonists can disrupt retention or consolidation when administered after the acquisition of information (Packard and Teather, 1997;Santini et al, 2001;McDonald et al, 2005) (but see Day and Langston, 2006). We found no evidence that ketamine (50 -100 mg/kg) affected retention when the drug was administered after the sample.…”
Section: Effects Of Ketamine On Encoding But Not Retentioncontrasting
confidence: 50%
“…This suggests that the "strength" of the encoded representation is weakened under the influence of ketamine (Kentros et al, 1998). Studies have shown that posttraining administration of NMDA antagonists can disrupt retention or consolidation when administered after the acquisition of information (Packard and Teather, 1997;Santini et al, 2001;McDonald et al, 2005) (but see Day and Langston, 2006). We found no evidence that ketamine (50 -100 mg/kg) affected retention when the drug was administered after the sample.…”
Section: Effects Of Ketamine On Encoding But Not Retentioncontrasting
confidence: 50%
“…209 for review] -although research to date has focused largely on the hippocampal side of the story. Consistent with this, the long-term retention of place memory (i.e., >24 h) is impaired by the blockade of NMDA receptor-dependent synaptic plasticity either before (see Synaptic plasticity and the rapid encoding of spatial information), or soon after, acquisition [210,211]. The latter finding suggests that the early stabilization of a memory requires additional offline episodes of NMDA receptor activation after the initial encoding event [see also refs.…”
Section: Cellular Consolidationmentioning
confidence: 74%
“…A similar pattern of results is observed following complete lesions of the hippocampus. Previous studies have shown that rats with anterograde damage to the hippocampus are consistently impaired on the acquisition of the spatial version of the water maze (Morris et al, 1982;Sutherland et al, 1983;Ferbinteanu and McDonald, 2003;McDonald et al, 2005). Furthermore, rats with anterograde damage to the hippocampus are not impaired at either fear conditioning to cue or context; however, rats with damage to the hippocampus after training impairs retention of fear conditioning to context but not to cue (Phillips and LeDoux, 1992;Sanders et al, 2003;Wiltgen et al, 2006).…”
Section: Discussionmentioning
confidence: 96%